Do environmental management systems affect the knowledge management process? The impact on the learning evolution and the relevance of organisational context. Issue 3 (14th February 2018) - Biscotti, Anna Maria; D'Amico, Eugenio; Monge, Filippo
Abstract : Purpose: The purpose of this study is to investigate how an environmental management system (EMS) might affect the environmental product innovation propensity of a firm through its influence on two factors shaping the knowledge process: the human capital management practices of training and development and the organisational context. Design/methodology/approach: To test the study's hypotheses, an empirical analysis was carried out on 262 companies drawn from 16 developed European markets included in the S&P Europe 350 Dow Jones index over the years 2005-2015.The authors adopted regression analysis by using the ordinary least squares and the binary logit econometric models. Findings: Consistently with the study's predictions, results show that for organisational contexts characterised by the presence of family owners, the EMAS-certified EMS reveals as a significant moderating factor that positively influences their approach to the knowledge management tools for the improvement of the workforce cognitive capabilities, with a significant impact on the firm's openness towards green product innovation. On the contrary, the ISO 14001-certified EMS tends not to stimulate such proactive behaviour, in both family and non-family firms. Practical implications: The findings suggest that an EMS can stimulate the knowledge exploration in the environmental protection field. To this end, top managers should overcome the bureaucratic vision of an EMS and conceive it as a knowledge management tool able to support the learning evolution of the organisation through an effective commitment to human capital management policies of training and development. Originality/value: Drawing from social identity and institutional theories, this is the first study – to the best of the authors' knowledge – that theorises and tests why the adoption of an EMS might stimulate the knowledge advancement of the organisation in a different way, especially in peculiar organisational contexts of family firms where the identity overlap between the family and the firm tends to affect the knowledge management process.